Constitutional domains democracy, community, management - Post, Robert, 1947- (Harvard University Press, 1995)
In a series of remarkable forays, Post develops an original account of how law functions in a democratic society. He draws on work in sociology, philosophy, and political theory, to offer a radically new perspective on some of the most pressing constitutional issues of our day, such as the regulation of racist speech, pornography, and privacy.